2017
DOI: 10.1021/jacs.7b02008
|View full text |Cite
|
Sign up to set email alerts
|

H-Bond Acceptor Parameters for Anions

Abstract: UV/vis absorption titrations have been used to investigate the formation of H-bonded complexes between anionic H-bond acceptors (HBAs) and neutral H-bond donors (HBDs) in organic solvents. Complexes formed by three different HBDs with 15 different anions were studied in chloroform and in acetonitrile. The data were used to determine self-consistent HBA parameters (β) for chloride, bromide, iodide, phosphate diester, acetate, benzoate, perrhenate, nitrate, triflimide, perchlorate, hexafluorophosphate, hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
106
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 61 publications
10
106
1
Order By: Relevance
“…For DT2–DT5 , binding to Cl − was found to be very weak ( K a <12 m −1 in all cases), but stronger binding was observed to the oxoanions with binding affinities decreasing across the series H 2 PO 4 − >AcO − >BzO − . This trend does not correlate with the basicity of the anions, in direct contrast to previous observations for the urea and squaramide compound series, nor does it correlate with the recently reported hydrogen bond acceptor parameter series, in which carboxylates are shown to be stronger hydrogen bond acceptors than − O 2 P(OR) 2 …”
Section: Resultsmentioning
confidence: 99%
“…For DT2–DT5 , binding to Cl − was found to be very weak ( K a <12 m −1 in all cases), but stronger binding was observed to the oxoanions with binding affinities decreasing across the series H 2 PO 4 − >AcO − >BzO − . This trend does not correlate with the basicity of the anions, in direct contrast to previous observations for the urea and squaramide compound series, nor does it correlate with the recently reported hydrogen bond acceptor parameter series, in which carboxylates are shown to be stronger hydrogen bond acceptors than − O 2 P(OR) 2 …”
Section: Resultsmentioning
confidence: 99%
“…When IL/2 ratio changes from 2 to 4, reduction of the yields of 5 and 6 is usually observed, probably owing to their further fluorination forming 8 and 9 (Scheme 3). It was found that the rate of formation of products 5, 6, 8 and 9 at lower temperature while using hydrophilic ionic liquids [ 22 The change of the cation part of IL has a small influence on the yield of fluorides ( Table 4). The results clearly show that total yields poorly correlate with the polarity of ionic liquids.…”
Section: Resultsmentioning
confidence: 99%
“…NMR titrations showed that even in polar MeCN,s ignificant association is seen. [16] Background titrations of 5,5'-dimethylbipyridine against 2h showed negligible interaction, demonstrating that the sulfonate group is responsible for the observed shifts of the N-H proton. Finally, N-alkylated substrates resulted in poor regioselectivity upon borylation with ligand 1a,e mphasizing the importance of the N À Hinorder to achieve high levels of regiocontrol and providing support for the crucial role of hydrogen bonding (Figure 3d).…”
Section: Angewandte Chemiementioning
confidence: 95%